2000
DOI: 10.1211/0022357001774994
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Pharmacodynamics and Pharmacokinetics of Candesartan and Losartan in Man

Abstract: The angiotensin II antagonistic effects of candesartan and losartan were compared in-vivo after single and repeated doses. Effects were related to antagonistic activity in plasma. In this double-blind, crossover study, 12 healthy male volunteers received, in random order, daily oral doses of 8 mg candesartan cilexetil or 50 mg losartan for seven days. On day 1 and day 8, dynamics and kinetics were assessed up to 48 h after dosing. Antagonistic effect was determined from the antagonist-induced rightward shifts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 9 publications
0
22
0
Order By: Relevance
“…Antagonism of AT1R by various ARBs has also been tested in vivo in humans, mostly healthy volunteers, and, similar to the above animal studies, this was largely done for ANGinduced blood pressure elevations. Following the original study with losartan (Christen et al, 1991), such studies have been performed with candesartan (Delacretaz et al, 1995;Ogihara et al, 1995;Belz et al, 1997Belz et al, , 2000Malerczyk et al, 1998;Fuchs et al, 2000;Gleiter et al, 2004), irbesartan (Belz et al, 1999Maillard et al, 1999;Mazzolai et al, 1999), losartan (Munafo et al, 1992;Belz et al, 1997Belz et al, , 1999Belz et al, , 2000Maillard et al, 1999;Mazzolai et al, 1999;Fuchs et al, 2000;Gleiter et al, 2004), telmisartan Stangier et al, 2001), and valsartan (Müller et al, 1994;Morgan et al, 1997;Belz et al, 1999Belz et al, , 2000Maillard et al, 1999;Mazzolai et al, 1999).…”
Section: Antagonism In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…Antagonism of AT1R by various ARBs has also been tested in vivo in humans, mostly healthy volunteers, and, similar to the above animal studies, this was largely done for ANGinduced blood pressure elevations. Following the original study with losartan (Christen et al, 1991), such studies have been performed with candesartan (Delacretaz et al, 1995;Ogihara et al, 1995;Belz et al, 1997Belz et al, , 2000Malerczyk et al, 1998;Fuchs et al, 2000;Gleiter et al, 2004), irbesartan (Belz et al, 1999Maillard et al, 1999;Mazzolai et al, 1999), losartan (Munafo et al, 1992;Belz et al, 1997Belz et al, , 1999Belz et al, , 2000Maillard et al, 1999;Mazzolai et al, 1999;Fuchs et al, 2000;Gleiter et al, 2004), telmisartan Stangier et al, 2001), and valsartan (Müller et al, 1994;Morgan et al, 1997;Belz et al, 1999Belz et al, , 2000Maillard et al, 1999;Mazzolai et al, 1999).…”
Section: Antagonism In Vivomentioning
confidence: 99%
“…By using such approaches it was found that candesartan yields a stronger inhibition of ANGinduced blood pressure elevation than losartan for a given level of receptor occupancy, indicating greater affinity and/or slower off-rate from receptor (Belz et al, 1997;Fuchs et al, 2000). Direct comparative studies from these investigators also showed an order of potency of irbesartan .…”
Section: Antagonism In Vivomentioning
confidence: 99%
“…Other authors observed different durations of action and different efficacies among four ARBs examined herein (21). Further, some studies have shown differences in antihypertensive effect among ARBs using ABPM (22)(23)(24). However, these studies have all been relatively short, with durations of about 1 month or, in the case of our own previous study, no more than 3 months.…”
Section: Introductionmentioning
confidence: 61%
“…Candesartan cilexetil (8 mg/d) and losartan (50 mg/d) for 7 days appeared to produce different pharmacodynamic effects as assessed by the rightward shift of the angiotensin II dose-response curve. In healthy volunteers the angiotensin II antagonistic effect of candesartan cilexetil was longer-lasting than that of losartan (31).…”
Section: Clinical Pharmacodynamicsmentioning
confidence: 82%